Respuesta :
-4.9t²+7.5t+1.8=2.1
-4.9t²+7.5t-0.3=0
t=-7.5±√(56.25-4*-4.9*-.3)/-2*4.9
t=-7.5±√(44.49/-9.8
t=(-7.5±6.67)/-9.8
t=-.83/-9.8 = .085 or t= -14.17/-9.8 = 1.446
-4.9t²+7.5t-0.3=0
t=-7.5±√(56.25-4*-4.9*-.3)/-2*4.9
t=-7.5±√(44.49/-9.8
t=(-7.5±6.67)/-9.8
t=-.83/-9.8 = .085 or t= -14.17/-9.8 = 1.446
Answer:
The equation in standard form is: [tex]-4.9t^{2} +7.5t-0.3=0[/tex]
The solutions for this equation are:
t1=0.0411
t2=1.4895
Step-by-step explanation:
The initial equation is: [tex]-4.9t^{2} +7.5t+1.8=2.1[/tex].
The standard form of a quadratic equation is:
[tex]a*t^{2} +b*t+c=0[/tex].
Where a, b and c are constants, to transform the initial equation into the standard form we should subtract from both sides of the equality the number 2.1 and simplify:
[tex]-4.9t^{2} +7.5t+1.8=2.1[/tex]
[tex]-4.9t^{2} +7.5t+1.8 - 2.1 = 2.1 - 2.1 [/tex]
[tex]-4.9t^{2} +7.5t+1.8 - 2.1 = 0 [/tex]
[tex]-4.9t^{2} +7.5t - 0.3 = 0 [/tex]
From this equation: a=-4.9, b=7.5 and c=-0.3
The solutions of a quadratic equation is given by the expressions:
[tex]t1=\frac{-b+\sqrt[2]{b^{2}- 4*a*c} }{2*a} \\[/tex]
[tex]t2=\frac{-b-\sqrt[2]{b^{2}- 4*a*c} }{2*a} \\[/tex]
Replacing the values of a, b and c and solving, we get:
[tex]t1=\frac{-7.5+\sqrt[2]{7.5^{2}- 4*(-4.9)*(-0.3)} }{2*(-4.9)} \\[/tex]
t1=0.04110
[tex]t2=\frac{-7.5-\sqrt[2]{7.5^{2}- 4*(-4.9)*(-0.3)} }{2*(-4.9)} \\[/tex]
t2=1.4895
Finally, the solutions of the quadratic equation are t1=0.04110 and t2=1.4895